2022
DOI: 10.2106/jbjs.21.01516
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Cement Augmentation Versus No Augmentation for the Fixation of Unstable Trochanteric Fractures

Abstract: Background:A previous randomized controlled trial (RCT) demonstrated a trend toward a reduced risk of implant-related revision surgery following fixation with use of a Proximal Femoral Nail Antirotation (PFNA) with TRAUMACEM V+ Injectable Bone Cement augmentation versus no augmentation in patients with unstable trochanteric fractures. To determine whether this reduced risk may result in long-term cost savings, the present study assessed the cost-effectiveness of TRAUMACEM V+ cement augmentation versus no augme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Cement application has been proposed as one option, with some studies showing improved quality of life and overall cost-effectiveness in addition to reducing the risk of complications in unstable trochanteric fractures. 28,29 Conversely, in the study by Bohringer et al, 30 cement augmentation did not reduce cutout compared with the conventional non–cemented-augmented blades and was associated with longer operative times and nearly double the cost. Concerns over cement extrusion into the joint during application, longer operative times, and increased costs still remain.…”
Section: Tips To Optimize Resultsmentioning
confidence: 89%
“…Cement application has been proposed as one option, with some studies showing improved quality of life and overall cost-effectiveness in addition to reducing the risk of complications in unstable trochanteric fractures. 28,29 Conversely, in the study by Bohringer et al, 30 cement augmentation did not reduce cutout compared with the conventional non–cemented-augmented blades and was associated with longer operative times and nearly double the cost. Concerns over cement extrusion into the joint during application, longer operative times, and increased costs still remain.…”
Section: Tips To Optimize Resultsmentioning
confidence: 89%
“…While Joeris et al 51 showed cost savings of $53.35/patient and quality-adjusted life-years (QALYs) gains of 0.01 quality-adjusted life-year/patient, Böhringer et al 16 showed no superiority for the augmented group. Joeris et al 51 assumed a high reintervention rate for the nonaugmented group 7.4% versus 1.6% in the augmented group, based on reported rates by Kammerlander et al 38 This study compared CMN with extramedullary fixation and the nails design in this study did not have rotational control, which might be the reason for the high reintervention reported rate and the reason for the different findings of the cost analyses. Other studies show that cement augmentation might facilitate improved functional outcome in the postoperative period including gait and weight-bearing abilities.…”
Section: Discussionmentioning
confidence: 99%
“…16 The cost of cement augmentation is not negligible, and conflicting results were published recently regarding the costeffectiveness of cement augmentation. While Joeris et al 51 showed cost savings of $53.35/patient and quality-adjusted life-years (QALYs) gains of 0.01 quality-adjusted life-year/ patient, Böhringer et al 16 showed no superiority for the augmented group. Joeris et al 51 assumed a high reintervention rate for the nonaugmented group 7.4% versus 1.6% in the augmented group, based on reported rates by Kammerlander et al 38 This study compared CMN with extramedullary fixation and the nails design in this study did not have rotational control, which might be the reason for the high reintervention reported rate and the reason for the different findings of the cost analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Various biomechanical studies were already able to demonstrate an increase in primary fixation strength compared to non-augmented proximal femoral nails [10]. A randomised clinical trial was able to demonstrate the safety of the augmentation of the femoral head with PMMA with comparable clinical outcomes and increased costeffectiveness due to reduced implant failure rates [13,27].…”
Section: Discussionmentioning
confidence: 99%